Maintenance of seed vigour and viability in sunflower (Helianthus annuus) hybrids and inbreds - Dadlani, Malavika; Varier, Anuradha; Mathur, Ruchi (The Indian Journal of Agricultural Sciences, 2012)
All expeiment was conducted during 1991-92 to study the loss of seed vigour and viability in 3 hybrids Â of sunflower (Helianthus annuus L.) and their parental lines under ambient conditions of storage. Hybrids ’LDMRSH 1’ and ’LDMRSH3’ showed better storability than their respective parents. Hybrid ’APSh 11 recorded less germination after storage than its parents. However, hybrids were superior to or at par with the better parent for seed and seedling vigour on the basis of dehydrogenase activity, electrolyte leakage, lipid peroxidation value and dry weight of seedling before and after storage.